Perancangan Mural sebagai Daya Tarik Wisata Alas Outbound Edukasi di Desa Simpang Kecamatan Prambon Sidoarjo - Hanafi Moeslim; Alfian Candra Ayuswantana (Jurnal Informasi Pengabdian Masyarakat, 2023)
Mural has now become a common media found in public spaces. In addition to being a means of information, murals also have interesting images and can have other functions, namely as a means of conveying messages, advertising materials, propaganda materials and even educational information documents. The making of this mural design will be applied to Community Service through the Independent Lecture Competency Program (PKKM) Bina Desa held by the Visual Communication Design Education Program of the National Development University "Veteran" East Java in Simpang Village, Prambon District, Sidoarjo Regency, East Java. The purpose of making the mural itself, among others, is to improve the aesthetics of tourist attractions as well as creating an attractive and beautiful visual appearance. This mural design will use design thinking approach. Design Thinking is a problem solving method that focuses on the user. This activity began on September 20, 2023 until October 25, 2023. The place of implementation is at the Alas Outbound Edukasi tourist spot in Simpang Village, Prambon District, Sidoarjo Regency, East Java. The PKKM Bina Desa collaboration between the Visual Communication Design Education Program of the National Development University "Veteran" of East Java and the Alas Outbound Edukasi tourism manager creates tourist attraction to visit Alas Outbound Edukasi Tourism, while providing cultural education for the community and visitors.